FORMATION OF LEAF SURFACE AND SOYBEAN VARIETIES PRODUCTIVITY ON USAGE OF INOCULATION, GREEN MANURE AND SPRAYING OF CROPS - Прус, Л. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The aim is to justify development and agro-technical measures varietal soybean growing technology areas in Western Lisostepu. Studies to stimulate the increase in the leaf surface of soybeans were carried out with the help of statistical analysis; field and laboratory experiments; consisted in the use of siderates; inoculation and treatment of crops with microbial preparations; laboratory and statistical analyzes. Studied the effect of factors on the formation of leaf surface and productivity of soybean varieties. Our research showed that the productivity of soybean seeds depended on the variety; the year growing and the factors and variations in the experiment. Discovered compositions give an opportunity to accelerate the growth and development of plants; increase the area of leaf surface; improve productivity and product quality.The highest yield soybean seeds received; on average for 2011-2015; by sort Georgiana - 3.04 t / ha; Angelica - 2;86t / ha; Ksenia - 2.94 t / ha and Legend - 2.81 t / ha. For example; productivity of of soybean seeds sort Ksenia under control without fertilizers without inoculation and without spraying was 2.55 t / ha; while the version with green fertilizer; it has increased up 2.77 t / ha. Spraying of crops by Hetomik boosted the yield to 2.68 t / ha. The use of green fertilizer; seed inoculation strain M-8 has provided yield 2.86 t / ha; strain 614A - 2;86 t / ha; with seed inoculation strain 634b on the background making green manure obtained the highest yield - 2.89 t / ha. Inoculation of seed by strains 634b; 614A; spraying of crops wiht Hetomik against the background of making green manure contributed to the increase of leaf surface soybean plants.